2011
DOI: 10.1590/s1415-43662011001200003
|View full text |Cite
|
Sign up to set email alerts
|

Adubação orgânica e inorgânica de batatinha em solos arenosos: produtividade, nutrientes na planta e lixiviação

Abstract: R ESU M OAs relações entre os teores de nutrientes em solos com adubação orgânica e inorgânica e os teores de nutrientes e produtividade de batatinha foram determinadas tal como as relações entre aportes e a lixiviação de N e bases trocáveis. Amostras de solo foram coletadas das camadas de 0-20, 20-40 e 40-60 cm em 18 áreas de produção com adições anuais de esterco variando entre 2 e 40 anos e, como controle, quatro áreas sob pastagem não adubadas. Amostras de solo e planta foram analisadas quanto aos teores d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
4
7
0
Order By: Relevance
“…A possible explanation for the quadratic behavior is the rapid mineralization of the organic compost, which has a low C/N ratio, indicating that application of higher quantities of this material can facilitate losses by leaching (Oliveira et al, 2011). Some authors have reported that the application of large quantities of organic materials with low C/N ratio can result in denitrification, which would explain the quadratic behavior observed in this study.…”
Section: Resultssupporting
confidence: 47%
“…A possible explanation for the quadratic behavior is the rapid mineralization of the organic compost, which has a low C/N ratio, indicating that application of higher quantities of this material can facilitate losses by leaching (Oliveira et al, 2011). Some authors have reported that the application of large quantities of organic materials with low C/N ratio can result in denitrification, which would explain the quadratic behavior observed in this study.…”
Section: Resultssupporting
confidence: 47%
“…The analysis was determined: pH in water 1:10 (m/v); electric conductivity (EC) 1:10 (m/v); total P (P t ) obtained by digestion with H 2 SO 4 and H 2 O 2 (Thomas et al 1967); P extracted with Mehlich-1 solution (MEP); P extracted with water (WEP) and the extracts determined by the method of Murphy and Riley (1962); WEC determined by the method of Mendonça and Matos (2005) adapted from Bartlett and Ross (1988); TOC obtained by wet oxidation-diffusion (Snyder and Trofymow 1984); and ash obtained by the method of EMBRAPA (2011) ( Table 4). The manure dose was calculated based on the content of P t in the cattle manure, considering the application of 16 Mg ha −1 in the first 20 cm of soil, which is the mean annual dose applied in the region (Galvão and Salcedo 2009;Oliveira et al 2011). However, we decided to apply 8 Mg ha −1 of cattle manure to the 0-10 cm layer to better observe P displacement.…”
Section: P-leaching Experiments With Soil Columnsmentioning
confidence: 99%
“…Soil in the columns was prepared manually, assuming a mean bulk density of 1.5 g cm −3 found for this type of soil (Santos et al 2012;Kang et al 2011;Oliveira et al 2011;Santos et al 2010). The layer of 0-10 cm was gently set, because the soil when plowed is less dense.…”
Section: P-leaching Experiments With Soil Columnsmentioning
confidence: 99%
“…In Brazil, annual applications of manure in areas with Dystric Xeropsamments of sandy texture in sub-humid region in the northeastern Brazil (Agreste) have caused accumulation of nutrients in the surface layer (Silva and Menezes 2007;Galvão et al 2008;Oliveira et al 2011). Consequently, these nutrients move down the soil profile, including phosphorus (Galvão and Salcedo 2009;Xavier et al 2009), which has little mobility in clayey soils.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of P in the topsoil increases the risk of its vertical displacement beyond the reach of the roots. This fact, in addition to representing an economic loss for the farmer, can become an environmental problem due to the contamination of subsurface water (Sharpley et al 2004;Nelson et al 2005;Galvão et al 2008;Oliveira et al 2011;Lee and Oa 2013).…”
Section: Introductionmentioning
confidence: 99%